Redesign Leak Test Machine For Part Cover Comp Head - Sumiyanto, Sumiyanto; Achyadi, Harwan (Green Publisher, 2023)
One of the aluminum casting component manufacturing companies produces Cover Comp Head parts that will be used on two-wheeled motorized vehicles. The customer provides that the parts produced must not leak at a pressure of 1 bar. The production demand from the customer is very high, so a redesign is needed in the form of a design for the leak tester in order to get an update on the leak test machine or the leak tester specifically for the main components of the leak tester, which are very directly related to the function of the leak tester. The method used in this redesign is the VDI 2221 method. Based on the results of the redesign carried out, it was found that the redesign concept of the comp head and tube hole compactors is more efficient in terms of dimensions and cost. So that it can provide direct benefits to the company.